Prediction of Thyroid Classes Using Feature Selection of AEHOA Based CNN Model for Healthy Lifestyle - Jopate, Rachappa; Pareek, Piyush Kumar; G, DivyaJyothi M.; Al Hasani, Ariam Saleh Zuwayid Juma (Majallat Baghdād lil-ʻulūm, 2024)
كثيرًا ما يعاني الأشخاص الذين يعانون من قصور الغدة الدرقية من أعراض حادة. يؤدي التصنيف الصحيح والتعلم الآلي إلى تحسين تشخيص أمراض الغدة الدرقية بشكل كبير. سيؤثر هذا التصنيف الدقيق على تقديم الرعاية للمرضى في الوقت المناسب. على الرغم من وجود تقنيات التشخيص، فإنها تسعى في كثير من الأحيان إلى التصنيف الثنائي، وتستخدم مجموعات بيانات كبيرة غير كافية، وتفتقر إلى تأكيد استنتاجاتها. تركز الأساليب الحالية على تحسين النموذج، في حين يتم إهمال هندسة الميزات. يقدم هذا البحث نموذج خوارزمية تحسين قطيع الفيل التكيفي   AEHOA  لاختيار السمات المثالية من أجل التحايل على هذه القيود. في البداية، استخدم طريقة تسمى تقنية الإفراط في أخذ العينات للأقلية الاصطناعية  SMOTE  لتسوية البيانات. وأخيرًا، يتم إدخال معلمات نموذج AEHOA في الشبكة العصبية التلافيفية  CNN  لتصنيف البيانات وتعزيز التنبؤ. تمت أيضًا زيادة دقة تنبؤات التصنيف عن طريق تعديل مجموعة البيانات. تم إخضاع مجموعتي البيانات لعملية تصنيف لإجراء مقارنة أكثر دقة للنتائج. People with underactive thyroids frequently endure severe symptoms. Correct classification and machine learning substantially improve thyroid disease diagnosis. This precise classification will impact the timely delivery of care to the patients. Although diagnostic techniques exist, they frequently seek binary categorization, use insufficiently big datasets, and lack confirmation of their conclusions. The focus of current approaches is on model optimisation, whereas feature engineering is neglected. This research presents the Adaptive Elephant Herd Optimisation Algorithm (AEHOA) model for selecting optimal attributes in order to circumvent these limitations. At first, employ a method called the Synthetic Minority Over-sampling Technique (SMOTE) to even out the data. Finally, the parameters of the AEHOA model are fed into a Convolutional Neural Network (CNN) to categorise data and enhance prediction. The accuracy of classification predictions was also increased by tweaking the dataset. Both datasets were put through a categorization process for a more precise comparison of results.